Rampancy of Antinematicidal Resistance Among Gastrointestinal Nematodes in Kurdish Goat Breeds - Kareem Khoshnow Hama; Fikry Ali Qadir (Zanco Journal of Pure and Applied Sciences, 2020)
The current study was designed to determine the emergence of resistance among gastrointestinal roundworms of native goats against renowned synthetic antinematicidals such as fenbendazole, avermectin and levamisole. To meet the survey requirements, six commercial goat farms, located in Sothern and Western Erbil province-Kurdistan region of Iraq, were chosen after performing qualitative parasitological assays. The study was executed from September to end of November, 2019. From each farm, 30 adult goats were haphazardly divided into two groups, a group (n=15) for treatment and other group (n=15) served as control. The faecal egg count reduction test (FECRT) and egg hatch assay (EHA) have disclosed emergence of resistance against fenbendazole. According to RESO Computer Program, the estimated FECR% in farms 1 and 2 were 70.72 and 79.55, whilst the lower confidence intervals 95% were 63 and 73.8 respectively. The LC50 value of fenbendazole after conducting EHA, calculated through probit analysis, was estimated to be 2.11 μg ml ־¹ (range 1.47-2.34). Regarding avermectin, the computed FECR% in farms 3 and 4 were 93.92 and 92.98, while the lower confidence intervals 95% were 92.91 and 90.7 respectively, which signified the presence of suspicion about prevalence of resistance against avermectin. For levamisole, the calculated FECR% in farms 5 and 6 were 95.99 and 96.38, whilst the lower confidence intervals 95% were 95.1 and 95.7 respectively. Consequently, the parasitic nematodes were susceptible to this synthetic chemotherapeutic in the region.